2023
DOI: 10.1002/adma.202306631
|View full text |Cite
|
Sign up to set email alerts
|

Structural Diversity of Single‐Walled Transition Metal Dichalcogenide Nanotubes Grown via Template Reaction

Yusuke Nakanishi,
Shinpei Furusawa,
Yuta Sato
et al.

Abstract: Monolayers of transition metal dichalcogenides (TMDs) are an ideal 2D platform for studying a wide variety of electronic properties and potential applications due to their chemical diversity. Similarly, single‐walled TMD nanotubes (SW‐TMDNTs)—seamless cylinders of rolled‐up TMD monolayers—are 1D materials that can exhibit tunable electronic properties depending on both their chirality and composition. However, much less has been explored about their geometrical structures and chemical variations due to their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…The difference in structural and electronic properties between nanotubes and nanoscrolls is worth noting. So far, TMDC nanotubes with small diameters have been studied theoretically , and recently synthesized around/inside carbon (or boron nitride) nanotubes. ,, Unlike nanotubes, nanoscrolls have nonclosed sheet structures and edges. Although the DFT calculations of nanoscrolls are difficult, we consider that these two structures have similar band structures, because the edge effect in nanoscrolls should be minor.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in structural and electronic properties between nanotubes and nanoscrolls is worth noting. So far, TMDC nanotubes with small diameters have been studied theoretically , and recently synthesized around/inside carbon (or boron nitride) nanotubes. ,, Unlike nanotubes, nanoscrolls have nonclosed sheet structures and edges. Although the DFT calculations of nanoscrolls are difficult, we consider that these two structures have similar band structures, because the edge effect in nanoscrolls should be minor.…”
Section: Resultsmentioning
confidence: 99%
“…However, it should be pointed out that, due to the strong strain effect caused by the curved surface, the growth efficiency and the diameter of the grown nanotube have been greatly limited. 16,17 Meanwhile, a variety of 1D vdWHs have been prepared by filling materials into the 1D cavity of nanotubes, 18 including molecules, 19−22 elements, 23−25 halides, 26−31 chalcogenides, 32−35 transition metal carbides, 36 and perovskites. 37,38 However, the low synthesis efficiency of 1D vdWHs materials and the fact that carbon nanotubes contain both semiconducting and metallic types 39,40 increase the difficulty of electrical study in 1D vdWHs.…”
mentioning
confidence: 99%
“…The coating method, which means attachment to the outer surface of a 1D material by vdW interaction, has been successfully used to obtain BN and MoS 2 nanotubes on the surface of single-walled carbon nanotubes (SWCNTs). However, it should be pointed out that, due to the strong strain effect caused by the curved surface, the growth efficiency and the diameter of the grown nanotube have been greatly limited. , Meanwhile, a variety of 1D vdWHs have been prepared by filling materials into the 1D cavity of nanotubes, including molecules, elements, halides, chalcogenides, transition metal carbides, and perovskites. , However, the low synthesis efficiency of 1D vdWHs materials and the fact that carbon nanotubes contain both semiconducting and metallic types , increase the difficulty of electrical study in 1D vdWHs. There has been little research on the electrical behavior and interlayer interaction of 1D vdWHs.…”
mentioning
confidence: 99%
“…We discuss the comparison of this study to previous studies. In the previous studies, structure-controlled heteronanotubes based on carbon nanotubes or boron nitride nanotubes were synthesized using the CVD method. In those approaches, due to the presence of metallic carbon nanotubes or the insulating nature of boron nitride nanotubes, there are still challenges in forming pure semiconducting nanotubes, i.e., pure semiconductor–semiconductor heterojunctions, which have unique optical properties and potential applications. On the contrary, TMDC nanotubes exhibit semiconducting properties regardless of their structure, , and their heteronanotubes have advantages in forming semiconductor–semiconductor heterojunctions. In this study, using the chalcogenization method, we demonstrated the production of semiconducting heteronanotubes with controlled structures such as layer number and crystallinity as well as the production of semiconducting heteronanotubes with specific chirality.…”
mentioning
confidence: 99%